Enteromius pinnimaculatus sp. nov. (Cypriniformes: Cyprinidae) from southern Gabon. Issue 5 (30th May 2019) - Mipounga, Hans Kevin; Cutler, Joseph; Mve Beh, Jean Hervé; Adam, Benjamin; Sidlauskas, Brian L.
Abstract: We present and describe a new species of Enteromius, adding to the 16 species of Enteromius currently recorded from Gabon, West Africa. This new species is distinguished from all other Gabonese Enteromius by the presence of several distinct spots on the dorsal fin in combination with three or four round spots on the flanks. In Africa, it is superficially similar to Enteromius walkeri and with which it shares an unusual allometry in that the proportional length of the barbels decreases as the fish grows. Nevertheless, one can distinguish these species by vertebral number, maximum standard length, the length of the anterior barbels, the length of the caudal peduncle and in most specimens, the number of lateral‐line and circumpeduncular scales. These two species also inhabit widely separated drainages, with E. walkeri occurring in coastal drainages of Ghana including the Pra and Ankobra Rivers and the new species occurring in tributaries of the Louetsi and Bibaka Rivers of Gabon, which are part of the Ogowe and Nyanga drainages, respectively. Despite extensive collections in those drainages the new species is known from only two localities, suggesting the importance of conservation of its known habitat.